2020
DOI: 10.34172/aim.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Coronavirus Disease 2019 and Influenza A: A Report from Iran

Abstract: Background: In late December 2019, a viral pneumonia known as coronavirus disease 2019 (COVID-19) originated from China and spread very rapidly in the world. Since then, COVID-19 has become a global concern and health problem. Methods: We present four patients in this study, selected from among patients who presented with pneumonia symptoms and were suspicious for COVID-19. They were referred to the intended centers for COVID-19 diagnosis and management of Shiraz University of Medical Sciences in southern Iran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 23 publications
1
78
1
4
Order By: Relevance
“…Secondary bacterial pneumonia can follow the initial phase of viral respiratory infection or occur during the recovery phase. 1 Data on SARS-CoV-2 is limited, but thus far, the overall incidence of viral co-infection has varied widely from 0% to 15% in different case series, [2][3][4][5][6][7] and combined viral and bacterial pneumonia rates appear to be low. 3,[8][9][10] There is also a dearth of data on the predisposing factors and causative organisms.…”
Section: ■ Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary bacterial pneumonia can follow the initial phase of viral respiratory infection or occur during the recovery phase. 1 Data on SARS-CoV-2 is limited, but thus far, the overall incidence of viral co-infection has varied widely from 0% to 15% in different case series, [2][3][4][5][6][7] and combined viral and bacterial pneumonia rates appear to be low. 3,[8][9][10] There is also a dearth of data on the predisposing factors and causative organisms.…”
Section: ■ Abstractmentioning
confidence: 99%
“…Co-infection and secondary bacterial infection • Viral co-infection incidence varies based on case series (0% to 15%) [2][3][4][5][6][7] • Combine bacterial and viral infection is rare in COVID-19 patients 3,8-10 • Secondary bacterial infection is not uncommon and leads to signifi cant morbidity and mortality, especially in the elderly 4,9,16 Procalcitonin • Detectable in 2 to 4 hours, peaks at 12 to 24 hours, and has a half-life of 25 to 30 hours • Levels are normal (< 0.5 μg/L) in COVID-19 patients with mild disease and may be elevated (≥ 0.50 μg/L) in patients with severe disease 10,14 • Elevated levels are correlated to a nearly 5-fold higher risk for severe SARS-CoV-2 infection 17 • Elevated levels are not specifi c to bacterial infection because they can also be raised in patients with acute respiratory distress syndrome, end-stage renal disease, cardiogenic shock, and multi-organ failure 18 • A normal level makes bacterial infection less likely and can guide antibiotic discontinuation 19,20 • In bacterial infection, levels may be less affected by IL-6 inhibitors than C-reactive protein (CRP) [21][22][23]…”
Section: Table 1 Key Points For Laboratory and Imaging Fi Ndingsmentioning
confidence: 99%
“…co-infection with COVID-19 and influenza and/or bacterial organisms. (46) It is possible that co-infection with more than one pathogen may be more frequent in HIV-infected persons or those with advanced immunosuppression. These unanswered questions will only be resolved once more data become available.…”
Section: Hiv-covid-19 Co-infected Personsmentioning
confidence: 99%
“…However, important knowledge gaps remain, particularly regarding the temporal profiles of viral load in association with disease severity of COVID-19. On the other hand, several studies have reported the co-infection of 2019-nCov with other respiratory virus, like Influenza A [7]. The co-infection indicates the possibility of viral interactions bearing on the course of infectious diseases [8,9].…”
Section: Introductionmentioning
confidence: 97%